Are Islamic Values Reduced and Dramatised in Memories of the Alhambra? - Nurhalisa; Nurhakki; Hayat, Nahrul; Iskandar; Wahyuddin; Marta, Rustono Farady (Kalijaga Journal of Communication, 2024)
This study aims to explore the plot and analyse the Islamic values in the Korean drama Memories Of The AlHambra and how they are displayed in the drama. The study method applies descriptive qualitative, with a semiotic analysis approach from Roland Barthes. The study results show that the drama Memories Of The AlHambra in denotation meaning, which tells a game created to find the lost game master with various conflicts. The connotation meaning is that these two characters have their own habits, a very high ambitious spirit related to the development of their company, J-One Holdings. The myth in this scene is very pro and con because many say religion should not be "dramatised". There is no theory that Fatima's hand is the key to heaven but in the drama Muslims believe Fatima's hand is the key to heaven, therefore there is a legend about the gate of justice on the day the key to heaven meets Fatima's hand, the gate will be opened and the AlHambra palace will collapse. As for Islamic values, they are found in the drama, namely, the value of worship, moral values, sharia values, moral values, and local wisdom values. There are plot principles in this drama, namely plot of actions, plot of characters and plot of though.